GABA(B) Receptors Expressed in Human Aortic Endothelial Cells Mediate Intracellular Calcium Concentration Regulation and Endothelial Nitric Oxide Synthase Translocation - Wang, Xu-Ping (Hindawi Publishing Corporation, 2014)
GABA(B) receptors regulate the intracellular Ca(2+) concentration ([Ca(2+)]i) in a number of cells (e.g., retina, airway epithelium and smooth muscle), but whether they are expressed in vascular endothelial cells and similarly regulate the [Ca(2+)]i is not known. The purpose of this study was to investigate the expression of GABA(B) receptors, a subclass of receptors to the inhibitory neurotransmitter γ-aminobutyric acid (GABA), in cultured human aortic endothelial cells (HAECs), and to explore if altering receptor activation modified [Ca(2+)]i and endothelial nitric oxide synthase (eNOS) translocation. Real-time PCR, western blots and immunofluorescence were used to determine the expression of GABA(B1) and GABA(B2) in cultured HAECs. The effects of GABA(B) receptors on [Ca(2+)]i in cultured HAECs were demonstrated using fluo-3. The influence of GABA(B) receptors on eNOS translocation was assessed by immunocytochemistry. Both GABA(B1) and GABA(B2) mRNA and protein were expressed in cultured HAECs, and the GABA(B1) and GABA(B2) proteins were colocated in the cell membrane and cytoplasm. One hundred μM baclofen caused a transient increase of [Ca(2+)]i and eNOS translocation in cultured HAECs, and the effects were attenuated by pretreatment with the selective GABA(B) receptor antagonists CGP46381 and CGP55845. GABA(B) receptors are expressed in HAECs and regulate the [Ca(2+)]i and eNOS translocation. Cultures of HAECs may be a useful in vitro model for the study of GABA(B) receptors and vascular biology.